Professional training of specialists as an important component of personnel policy in the sphere of civil protection - Kryvoruchko, Iryna (Theory and Practice of Public Administration, 2025)
The article is devoted to the analysis of professional training of specialists in the formation of an effective personnel policy in the sphere of civil protection of Ukraine and the development of scientifically based recommendations for its improvement, taking into account modern challenges. An urgent need to revise and improve the personnel policy of civil protection, due to key determinants, was identified. A set of regulatory and legal documents on professional education, training of specialists in the sphere of civil protection was studied. The features of the system of training specialists in the sphere of civil protection were identified. The role of the State Emergency Service of Ukraine in the professional training of specialists in the sphere of civil protection was emphasized. The focus was on the adaptation of newly appointed employees to enhance the efficiency of the work of the State Emergency Service of Ukraine and reduce staff turnover as an important component of further professional growth. The mechanism for conducting training of management and specialists whose activities are related to the organization and implementation of civil protection measures is described. The principles of educational activities for functional training of educational and methodological centers in the field of civil protection are determined. The absence of a holistic system of continuous anti-stress training of specialists in the field of civil protection at all stages of their professional development is established. The emphasis is placed on increasing the effectiveness of the formation of psychological readiness of cadets for activities in risky circumstances. It is substantiated that the integration processes of Ukraine actualize the need to improve the quality of foreign language training of future specialists in the field of civil protection in higher education institutions with special training conditions, and areas for improvement are identified. To improve the quality of state personnel policy in the field of civil protection, areas of optimization are proposed. Professional training of specialists in the field of civil protection is considered the key to the effectiveness of the activities of the Civil Protection Service of Ukraine. A characteristic feature of this training is the formation of the content of professional training taking into account the competency, activity and interdisciplinary approaches.